Paw patrol. Rescue wheels [videorecording (DVD)] (Paramount, 2024)
When Bull Mastiff, Boomer, and his ferret friend roll into Adventure Bay they₂re both eager to show everyone that they₂re the loudest, meanest monster truck drivers ever including being as destructive as possible! How will Ryder and the pups stop Boomer? With all-new, spinning, crashing, jumping, climbing, hauling Rescue Wheels of their own with graphic suits to match! Together, with their new, highly skilled, Rescue Wheels female pup pal Roxi, Ryder and the pups will put on a spectacle of their own as they stop Boomer and take on rescues in extreme environments only their new Rescue Wheels can get them to. When you have mega, monster-sized missions, you need Rescue Wheels! Includes over 2 hours of roarin₂ adventures!